METAPHOR IN SELECTED POP SONGS OF BATAK TOBA - Hiace Vega Fernando Siahaan; Andi Jaihutan Silitonga; Mega Silvia Sihombing (LPPM Universitas Darma Agung, 2021)
This research article focused on analyzing metaphor in selected pop songs of Batak Toba. This study used qualitative research in analyzing the data. The data of this study were the lyrics pop songs of Batak Toba. There were ten pop songs of Batak Toba analyzed in this study. The results of the study shown there were seven types of metaphor used in selected pop songs of Batak Toba. The seven types of metaphor used were: active metaphor consist of 13 lyrics (30,2%), approximation metaphor consist of 8 lyrics (18,6%), mimetic metaphor consist of 6 lyrics (13,9%), phenomenalistic metaphor consist of 6 lines (13,9%), subjective metaphor consist of 5 lyrics (11,6%), symbolism metaphor consist of 3 lyrics (6,9%), precision metaphor consist of 2 lyrics (4,6%). The most dominant type of metaphor that was used in selected pop songs of Batak Toba was active metaphor with the percentage 30,2%.